Breaking Bars: An investigation into how performance art as an intervention program inside prison may lead to a behavior change among male gang members in Cape Town, South Africa - Lingaas, Ingebjørg (2019)
Violence has been declared a public health problem by the World Health Organisation (1996). Violence prevention strategies are actively used in efforts to rehabilitate offenders during their incarceration, and are intended to prepare them for reintegration into society and to prevent recidivism. Given the lack of research undertaken on violence prevention strategies in the gang-ridden context of Cape Town, South Africa, this dissertation looks at a prison intervention programme, Help I am Free, that uses performance arts as a case study to investigate the potential impacts of such intervention strategies. The paper does so by outlining the experiences of five male gang members before, during, and after their time in prison. Using a cross-sectional qualitative research design, the dissertation explores participants’ life histories and seeks to shed light on the ways in (and degrees to) which such programmes may influence the men’s attitudes towards themselves and others, and the likelihood of their successful reintegration into society. The theoretical frameworks used draw on applied theatre theories, social-cognitive theories, and theories of masculinities. The paper argues that programmes such as Help I am Free may impact participants’ perceptions of self and others strongly, and may also lead to an increased sense of self-worth and motivation to change lifestyle. However, it also indicates the limitations of the programme to achieve sustained success, given the structural barriers which afflict South Africa. The paper outlines a number of challenges that the men face while on parole, and concludes that while prison intervention programmes, and art programmes specifically, may trigger a sense of healing and encourage more positive notions of self, there are more comprehensive strategies in post-release urgently needed in order to prevent recidivism and to achieve authentic social re-integration